Cloud Accounting and Operational Efficiency of Tier 1 Banks in Nigeria: Leveraging on Technological Competence - Ighosewe, Enaibre Felix; Onatuyeh, Edwin Aruobogha; Udo-Ezika, Dave; Agbogun, Oghenekparobo Ernest; Uwhejevwe-Togbolo, Samuel Ejiro (Journal of Ecohumanism, 2024)
The integrative research examined the nexus between cloud accounting, technological competence, and operational efficiency, with a focus on the mediating role of bank staff's technologically competent. Data were collected from 341 staff members of selected banks through a questionnaire and was analyzed via partial least squares structural equation modeling (PLS-SEM). The findings reveal that technological competence enhances cloud accounting costs, interfaces, and delivery modes, thereby improving the operational efficiency of the banks studied. The study concludes that technological competence is crucial in optimizing the relationship between cloud accounting and operational efficiency. This underscores the importance of technological expertise in realizing the benefits of cloud-based technologies, particularly in achieving greater operational efficiency for banks. By concentrating on the Nigerian banking sector, the study offers context-specific insights into the interplay between cloud accounting, technological competence, and banks' operational performance. The study recommends that bank managers should compare their performance against industry average (benchmark), identify areas that need improvement, and institute corrective measures to drive operational excellence and achieve strategic objectives.